The Starbucks® School of Language Acquisition: A Cheap,CaffeinatedPlan to Prepare for Academic Study - Jeff McQuillan (Universitas Islam Malang, 2020)
Many international students enroll in yearlong Intensive English Programs (IEP) in English-speaking countries in the hope of acquiring the language proficiency necessary for academic study. Nation (2006) estimatedthatthese students need to know between 8,000 and 10,000 of the most commonly used word families in English to havegood comprehension of adult-level texts. There is considerable evidence, however, that reading for pleasureis at least as effective as formal study inboosting vocabulary knowledge (Krashen, 2004), including academic vocabulary (McQuillan, 2019).